GOVERNMENT STIMULATION OF TOURISM DEVELOPMENT IN RUSSIAN FEDERATION - Sroślak, Grzegorz (Acta Scientiarum Polonorum. Oeconomia, 2010)
Current state of tourism in R.F. is imfl uenced by two main groups of causes. On one side we have a pool of materials and resources, followed by the society demands created in the previous political system, while on the other hand we have the economical condition of the society [very diversed] and its actual state of knowledge and demands. As a result it led to reation of peculiar tendencies on the tourism market in Russia. There is a growth in the number of costly endeavours organised by the travel agencies, had caused a noticeable rise in the number od wealthy clients, which, on the other side is accompanied by a low – budget of vacations organised by the people on their own, sometimes even as tramps. The task of resolving those problems is lying in the hand of of the Russian Federation administration which utilises a number of organisational, legislational and financial initiatives.They are mainly used at once and that results in stimultaion of tourism in corelation to objectives of tourism and macroeconomic politics.